Investigation of perceived stress and attention deficit and hyperactivity disorder in shooters according to some variables - Zekiye Özkan; Gülçin Güler; Sanem Şehribanoğlu (ROL Spor Bilimleri Dergisi)
Attention, focus and concentration are vital components of shooting. Therefore, Attention Deficit Disorder and Hyperactivity Disorder (ADHD) as well as perceived stress are among the factors that significantly affect an athlete’s performance. This study aims to examine the cases of ADHD and PS in shooters and the correlation between these two variables. The study was conducted with 200 shooters. The ASRS was administered to measure ADHD of the participants and the PSS was used to measure their PS levels. Mann-Whitney U test, Spearman correlation, and Structural Equation Modeling (SEM) analyzes were performed. The findings of study revealed the ASRS and PSS total and sub-dimension scores of the shooters were found to be low. According to gender results, the ASRS and PSS scores of female athletes were significantly higher than those of males (p < .05). Also, it was found a positive and significant correlation between the total scores of ASRS and PSS of the shooters (rspearman = 0.47, p < 0.00). According to the SEM results, ADHD has a positive effect of 0.66 on PS. In conclusion, it is believed that shooting sports positively affect ADHD and PS by minimizing their symptoms since they require high levels of attention, also, it would be beneficial to direct individuals with ADHD to sports that require focus, such as shooting.